1999
DOI: 10.1159/000055271
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinedione Induces Apoptosis and Monocytic Differentiation in the Promyelocytic Leukemia Cell Line HL60

Abstract: Thiazolidinedione (TZD) is known to be a potent activator of peroxisome proliferator-activated receptor γ (PPARγ), a nuclear receptor that constitutes a heterodimer with retinoid X receptor (RXR). Since a considerable amount of PPARγ is expressed in various hematopoietic cells, the present study was undertaken to examine the effect of TZD in the absence or presence of LG100268, an RXR-selective ligand, on a cultured promyelocytic leukemia cell line, HL60. Treatment with TZD (25–50 µM troglitazone or pioglitazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 22 publications
3
26
0
Order By: Relevance
“…Apoptosis induction by PPARg ligands has been demonstrated in a variety of cell lines (Elstner et al, 1998(Elstner et al, , 2002Mueller et al, 1998;Kitamura et al, 1999;Takahashi et al, 1999;Chang and Szabo, 2000;Padilla et al, 2000;Tsubouchi et al, 2000;Eibl et al, 2001, Kawa et al, 2002. In the HL60 leukemia cell line, TG suppressed cell proliferation and induced apoptosis at concentrations of 25-50 mM (Hirase et al, 1999), which were similar to what we used in our experiment. The authors of the above study suggested that TG-induced apoptosis and differentiation might be mutually associated.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Apoptosis induction by PPARg ligands has been demonstrated in a variety of cell lines (Elstner et al, 1998(Elstner et al, , 2002Mueller et al, 1998;Kitamura et al, 1999;Takahashi et al, 1999;Chang and Szabo, 2000;Padilla et al, 2000;Tsubouchi et al, 2000;Eibl et al, 2001, Kawa et al, 2002. In the HL60 leukemia cell line, TG suppressed cell proliferation and induced apoptosis at concentrations of 25-50 mM (Hirase et al, 1999), which were similar to what we used in our experiment. The authors of the above study suggested that TG-induced apoptosis and differentiation might be mutually associated.…”
Section: Discussionsupporting
confidence: 83%
“…In hematopoietic cells, peripheral mononuclear cells and several human leukemia cell lines have been reported to express PPARg (Greene et al, 1995). TZD initiates monocytic differentiation in the promyelocytic leukemia cell line HL60 and induces apoptosis at a high concentration (Hirase et al, 1999). PPARg expression and its significance in apoptosis have also recently been evaluated in human B lymphocytes (Padilla et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…TRO was shown to causes apoptosis of many different cell lines including: endothelial cells, monocyte-derived macrophages (Chinetti et al, 1998), six colon cell lines (Kitamura et al, 1999), HL60 promyelocytic leukemia cells (Hirase et al, 1999), and vascular smooth muscle cells (Okura et al, 2000). TRO was recently shown to induce apoptosis in human liver cancer cells (Toyoda et al, 2001(Toyoda et al, , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…These lipidsensitive receptors can be activated in a variable isotypespecific manner by natural fatty acids, leukotrienes, prostaglandins, and some synthetic agonists, including antidiabetic drugs, such as rosiglitazone, ciglitazone, and pioglitazone. These drugs are also effective in regulating cell activation, differentiation, proliferation, and/or apoptosis (3,4).…”
Section: Introductionmentioning
confidence: 99%